Progress in tension-relieving suturing surgery: revolutionary surgical techniques and patient prognosis evaluation methods - Ge, Maolong; Zheng, Weifeng; Yao, Ping; Gao, Lin; Ge, Xinyang; Zhang, Qixin; Wang, Xiaolin; Guo, Chuangju (Frontiers in Surgery, 2025)
During the repair of skin and soft tissue wounds, excessive tension frequently leads to delayed healing, hypertrophic scarring, and tissue inflammation. Consequently, reducing skin or soft tissue tension has emerged as a crucial measure to facilitate wound healing. Tension-relieving suture procedures achieve this by adjusting incision design or employing specialized suturing techniques to release or diminish the tension at the wound margins, thereby improving local blood circulation and cellular signaling, promoting wound closure, and reducing scar formation. The super-tension-relieving suture procedure, an innovative advancement in tension-relieving technology, utilizes slowly absorbable barbed sutures to extend the duration of tension relief. This method is particularly advantageous in cases involving large excision areas and high tension, as it offers significant benefits over traditional techniques in terms of suturing approach, tension dispersion, and local stress regulation, thereby more effectively preventing hypertrophic scars. Moreover, preliminary studies suggest that it exerts a positive impact on the management of keloids. This review comprehensively examines the evolution, design principles, and clinical applications—with evidence-based outcomes—of tension-relieving suture techniques across multiple disciplines, including plastic surgery, cardiovascular surgery, neurosurgery, and orthopedics. By integrating a wealth of literature and clinical data, the paper aims to elucidate the significant benefits and future prospects of tension-relieving strategies in enhancing wound repair quality, lowering scar risk, and advancing surgical innovation.